‘Author and Authorship’ in Scientific Journals - Shah, Jay N (Journal of Patan Academy of Health Sciences, 2015)
DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13006 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):1-3